Nitric oxide and hydrogen peroxide independently act in mitigating chromium stress in Triticum aestivum L. seedlings Regulation of cell death, chromium uptake, antioxidant system, sulfur assimilation and proline metabolism - Singh, Samiksha (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.